1956
DOI: 10.1002/jsfa.2740070606
|View full text |Cite
|
Sign up to set email alerts
|

Heat and water transfer during the dehydration of herring fillets

Abstract: The. rate of drying of herring fillets in an over-draught dryer was very sensitive to temperature, but practically unaffected by normal ranges of wet-bulb depression and air velocity. Fatty herrings took longer to dry than lean ones and considerable fat oxidation occurred during the process. Variation of thickness within the range usually encountered was of some importance.The storage life of fillets, which depends very much on taste, was limited chiefly by ( I ) the oxidation of the fat, which could be preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Del Campo et al (1956) found that fatty herrings took longer to dry than lean ones, and that considerable fat oxidation occurred during the process. Finally, Lintoh et al (1945), studying the drying of heavily-salted cod, reported that the optimum drying conditions for this product were: air velocity of 100 to 125 cm/set, air temperature of 26°C and relative humidity of 45 to 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Del Campo et al (1956) found that fatty herrings took longer to dry than lean ones, and that considerable fat oxidation occurred during the process. Finally, Lintoh et al (1945), studying the drying of heavily-salted cod, reported that the optimum drying conditions for this product were: air velocity of 100 to 125 cm/set, air temperature of 26°C and relative humidity of 45 to 55%.…”
Section: Introductionmentioning
confidence: 99%